Overview Of Knowledge And Near Miss Reporting By Employees At The Mine Office Pt Mifa Bersaudara - Nurafiza, Nurafiza; Anwar, Sufyan; Paradhiba, Meutia; Musnadi Is, Jun; Firdauz Saputra, Firman (Teewan Solutions, 2024)
When accidents and possible workplace hazards are reported, it helps to determine what went wrong and can be used as a basis for future safety measures. Instilling the need to report Near miss in employees is driven by this. Knowing how well the Mine Office of PT Mifa Bersaudara knows about Near miss and how often they are reported is the main objective of this study. The research strategy of this study is descriptive and quantitative. The research was conducted in December 2023 at the Mine Office of PT Mifa Bersaudara. The total population was 91, and 48 individuals were randomly selected using the slovin formula. The variables of this study are knowledge, near miss reporting and constraints in near miss reporting. The results showed that the majority of workers had good knowledge, namely 43 people (89.6%) with the majority of workers not reporting near miss events, namely 39 people (81.3%), and workers had obstacles in reporting near miss events, namely 34 people (70.8%). The conclusion of this study is that the near miss reporting system is still not optimal despite the fact that organizations use near miss reports for continuous improvement, near miss reporting procedures are very easy, easy to understand, and use basic and straightforward forms. In accordance with the criteria set by the Production Department of PT Mifa Bersaudara, the business should investigate the reasons for unmet near miss reporting components.